Comparative study of three phenoloxidases in the sea cucumber Apostichopus japonicus. Issue 67 (August 2017) - Jiang, Jingwei; Zhou, Zunchun; Dong, Ying; Chen, Zhong; Sun, Hongjuan; Yang, Aifu; Gao, Shan; Su, Hesheng
Abstract: In order to preliminarily illustrate the functional differences of phenoloxidases (POs) in Apostichopus japonicus, the full-length cDNAs of two POs (named as AjPOⅡ and AjPOⅢ, respectively) were cloned from the coelomocytes of A. japonicus using 3′- and 5′-rapid amplification of cDNA ends method, and combined with the previously acquired full-length cDNA of a laccase-type PO from A. japonicus (Accession No.KF040052, named as AjPOⅠ), the sequence structure and phylogenic status of POs from A. japonicus (AjPOs) were comparatively analyzed, and the transcriptional expression of AjPOs in different tissues, at different developmental stages and after different bacterial challenges was determined with quantitative real-time PCR method. Sequence analysis indicated AjPOⅡ and AjPOⅢ were both laccase-type POs, coincident to the results of phylogenic analysis. Sequence analysis also showed that AjPOⅠ had a transmembrane domain (J. Jiang et al., 2014), AjPOⅡ contained a signal peptide, and AjPOⅢ possessed a signal peptide and a transmembrane domain, implying that three AjPOs might play different roles in immune and physiological processes. Transcriptional expression analysis showed that AjPOⅡ and AjPOⅢ were most abundant in tube feet, while AjPOⅠhad the highest expression level in coelomocytes (J. Jiang et al., 2014), suggesting that AjPOⅠ may be mainly involved in immune response, while AjPOⅡ and AjPOⅢ are probably responsible for other physiological processes in addition to immune response. Besides, three AjPOs were determined to have different expression patterns during organism development and different spectrums of response against bacteria, which further indicated that there might be immune and physiological functional differentiation among three AjPOs. Highlights: Three phenoloxidases (POs) from Apostichopus japonicus were comparatively studied. Three A. japonicus POs (AjPOs) contain different structure domains. Three AjPOs show difference in tissue distribution and developmental expression. Three AjPOs have different spectrum of response against bacteria. There might be functional differentiation among three AjPOs.